Peningkatan Pengetahuan Teknik Pengemasan dan Keamanan Pangan Penjaja Makanan Bendhung Lepen Yogyakarta - Rahmadewi, Yunda Maymanah; Ayuningtyas, Cita Eri (UKInstitute, 2022)
Not all street food vendors understand the packaging and food safety aspects. This can be seen from the observations of food handler in the ecotourism of Bendhung Lepen’s street food, Yogyakarta. Though both of them are important aspects to consider in order to produce safe food. Therefore, education is needed with the aim of to increase the knowledge and skills of the community, especially street food vendors, in practicing good product packaging and implementing food safety.This empowerment was carried out using counseling and training methods consisting of several activities. The activities carried out were preparation, socialization, implementation, and evaluation. The targets of this program were street food handlers and vendors in the ecotourism of Bendhung Lepen Yogyakarta.The results that obtained were an increase in the knowledge and skills of participants from Bendhung Lepen ecotourism street food handlers and vendors. In addition, target communities become more skilled in packaging products and implementing food safety aspects. This increase can be a provision to produce safe products.